Determinan Angka Partisipasi Sekolah SMP di Jawa Barat - Khairunnisa, Khairunnisa; Hartoyo, Sri; Anggraeni, Lukytawati (UI Scholars Hub, 2014)
West Java province's junior secondary school enrollment rate is still below the Millennium Development Goal of universal primary education by 2015. Panel data of 26 districts in West Java, Indonesia, was used to analyze the determinant factors of junior secondary school enrollment rate. The study shows that GRDP per capita and education level of the household head positively influence junior secondary enrollment rate, in contrast poverty rate and number of child labour had negative impact. This study suggests that government should increase local revenue to enable the people to have sufficient income for attending school, especially for the poor. The government is also expected to increase the availability of schools.